Manifestation and consequences of warming and altered heat fluxes over the Bering and Chukchi Sea continental shelves. (July 2020) - Danielson, S.L.; Ahkinga, O.; Ashjian, C.; Basyuk, E.; Cooper, L.W.; Eisner, L.; Farley, E.; Iken, K.B.; Grebmeier, J.M.; Juranek, L.; Khen, G.; Jayne, S.R.; et al.
Abstract: A temperature and salinity hydrographic profile climatology is assembled, evaluated for data quality, and analyzed to assess changes of the Bering and Chukchi Sea continental shelves over seasonal to century-long time scales. The climatology informs description of the spatial distribution and temporal evolution of water masses over the two shelves, and quantification of changes in the magnitude and throughput of heat and fresh water. For the Chukchi Shelf, linear trend analysis of the integrated shelf heat content over its 1922–2018 period of record finds a significant summer and fall warming of 1.4 °C (0.14 ± 0.07 °C decade −1 ); over 1990–2018 the warming rate tripled to 0.43 ± 0.35 °C decade −1 . In contrast, the Bering Shelf's predominantly decadal-scale variability precludes detection of a water column warming trend over its 1966–2018 period of record, but sea surface temperature data show a significant warming of 0.22 ± 0.10 °C decade −1 over the same time frame. Heat fluxes over 1979–2018 computed by the European Centre for Medium-Range Weather Forecast (ECMWF) ERA5 reanalysis exhibit no record-length trend in the shelf-wide Bering surface heat fluxes, but the Chukchi Shelf cooling season (October–March) has a trend toward greater surface heat losses and its warming season (April–September) has a trend toward greater heat gains. The 2014–2018 half-decade exhibited unprecedented low winter and spring sea-ice cover in the Northern Bering and Chukchi seas, changes that coincided with reduced springtime surface albedo, increased spring absorption of solar radiation, and anomalously elevated water column heat content in summer and fall. Consequently, the warm ocean required additional time to cool to the freezing point in fall. Fall and winter ocean-to-atmosphere heat fluxes were anomalously large and associated with enhanced southerly winds and elevated surface air temperatures, which in turn promoted still lower sea-ice production, extent, and concentration anomalies. Likely reductions in sea-ice melt were associated with positive salinity anomalies on the Southeast Bering Shelf and along the continental slope over 2014–2018. Negative salinity anomalies during 2014–2018 on the central and northern Bering Shelf may be related to a combination of 1) long-term declines in salinity, 2) an increase of ice melt, and 3) a decline of brine production. We hypothesize that freshening on the Bering Shelf and in Bering Strait since 2000 are linked to net glacial ablation in the Gulf of Alaska watershed. We show that the heat engines of both the Bering and Chukchi shelves accelerated over 2014–2018, with increased surface heat flux exchanges and increased oceanic heat advection. During this time, the Chukchi Shelf delivered an additional 5–9 x 10 19  J yr −1 (50–90 EJ yr −1 ) into the Arctic basin and/or sea-ice melt, relative to the climatology. A similar amount of excess heat (60 EJ yr −1 ) was delivered to the atmosphere, showing that the Chukchi Sea makes an out-sized contribution to Arctic amplification. A conceptual model that summarizes the controlling feedback loop for these Pacific Arctic changes relates heat content, sea ice, freshwater distributions, surface heat fluxes, and advective fluxes.